Revision of the legal system for the protection of persons with disabilities due to the International Convention on the Rights of persons with disabilities. Special reference to people suffering from severe cerebral palsy (Revista de derecho aragonés, 2021)
The aims of this project are: (i) to present a critical vision of the Bill based on the Convention on the Rights of Persons with Disabilities; (ii) to describe the current situation of Spanish legislation regarding people with severe disabilities, with special reference to people who suffer from severe cerebral palsy. All this to detail what they need for an effective legal capacity, among other things. As a result, a critical vision of the Bill will be given and those aspects that it does not contemplate and that are necessary for its viability will be mentioned.
Keywords: curatorship; bill; disability; functional diversity; Civil code modifications due to the International Convention on the rights of persons with disabilities